Outsourcing, competitiveness and the labour market: losers and winners - Fontagné, Lionel (Papeles de Europa, 2009)
This article aims at briefly surveying the evidence of outsourcing, considering its impact on the labour market in advanced economies. On the base of the process definition, a tentative assessment of the overall impact of trade with low wage economies is proposed and after that the article addresses two policy-related issues: through which channels does trade with low wage countries (according to a broad definition of outsourcing) impact the labour market? And what are ultimately the patterns of international specialisation after outsourcing has taken place? The three conclusions are that outsourcing is the clue to understand the observed changes in labour demand; that product upgrading, and reshaping of production processes on an extended European basis, has preserved European competitiveness; and that top range varieties produced at low cost thanks to outsourcing have been key to such competitiveness.